geometry

If m fcg= 9x+3 and gcb= 13x-9
Find gcb

  1. 👍 0
  2. 👎 0
  3. 👁 225
asked by Stacey
  1. Didn't you just state that gcb = 13x - 9 ?

    I have no clue what gcb is, or what m fcg is.

    1. 👍 0
    2. 👎 0
    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    If m∠FCG = 9x + 3 and m∠GCB = 13x – 9, find m∠GCB

    asked by Anonymous on July 3, 2017
  2. algebra

    Find an equation for a line that has a slope of -13 and contains (-7, 2) Answer choices 1. y = -13x - 89 2. y = 13x + 93 3. y = -13x + 19 4. y = 13x - 33

    asked by Joe on March 10, 2018
  3. math/algebra

    subtract. express in simplest form 13x/30 - 4x/ 15 = factor the first denominator. Get a common denominator. Combine terms. I will be happy to critique your work. ok 13x/30 - 4x/ 15 = This is where I get lost, I know that I have

    asked by Diana on July 15, 2007
  4. Algebra

    Can you pleas Solve the quadric equation step by step 4x square =13x+2 4x^2 = 13x + 2 subtract 13x and 2 from both sides 4x^2 - 13x - 2 = 0 Now use the quadratic formula, since it does not factor.

    asked by Tony on April 11, 2007
  5. intermidate algebra

    Solve each equadratic equation by factoring. 6^2-13x-28 36-13x-28 -13x=-36+28 x=64/13 check this, correct if wrong

    asked by Angelia on May 17, 2010
  6. polynomials naman

    If remainder on division x^3-kx^2+13x-21 by 2x-1 is -21 ,find quotient and k.Hence find zeroes of cubic polynomial x^3 -kx^2+13x-21.

    asked by pankaj khanna on July 2, 2015
  7. algebra2

    Solve each of the following quadratic equations. can some explain how to do these kinds of problems 4x^2=13x+12 i believe if i am understanding this i am supose to add to where i get =0 4x^2-13x+12=0 now what do i need to do I am

    asked by Tina on May 9, 2007
  8. algebra

    6^2-13x-28 36-13x-28 -13x=-36-28 x=8/13 could you check this problem it had to be done and turn in tonight.

    asked by Johnnie J on May 17, 2010
  9. Algebra

    Hello all - I would like to check my work on 2 problems. Solve by factoring : x^2-13x= -12 x^2-13x+12= -12 + 12 x^2-13x+12= 0 (x-1)(x-12)= 0 x = 1 , 12 Solve using the square root property: 2x^2-35=15 2x^2-35-15=0 2x^2-50=0

    asked by John on November 12, 2007
  10. Calculus

    Let 5x^2 - 3xy + 58 = 2y^3 Use implicit differentiation to find y' for the above equation. The first thing I did was move 2y^3 over to that everything is equal to 0. With the -3xy I used the product rule and expanded that. After

    asked by Nira on March 5, 2017

More Similar Questions